1998
DOI: 10.1068/p271317
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Binocular Disparity and Motion Parallax in Determining Perceived Depth and Perceived Size

Abstract: Although binocular disparity and motion parallax are powerful cues for depth, neither, in isolation, can specify information about both object size and depth. It has been shown that information from both cues can be combined to specify the size, depth, and distance of an object in a scene (Richards, 1985 Journal of the Optical Society of America A 2 343-349). Experiments are reported in which natural viewing and physical stimuli have been used to investigate the nature of size and depth perception on the basis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…A judgment based on surfaces (at a range of disparity corrugation frequencies to establish a comprehensive picture of the disparity sensitivity functions) was used to determine sensitivity as opposed to judging depth order of two lines. In addition, the stimuli were presented in more naturalistic conditions in which many cues to distance are present (Durgin et al, 1995;Glennerster et al, 1996;Frisby et al, 1996;Bradshaw et al, 1998;O'Leary & Wallach, 1980;Predebon, 1993) and the range of viewing distances included a relatively near one (28.5 cm). We also took care, through the use of artificial pupils, that changes in pupil size and accommodative state, which would normally co-vary with viewing distance, would not also change with viewing distance and thereby cause a change in stereoacuity.…”
Section: Figure 1 About Herementioning
confidence: 99%
“…A judgment based on surfaces (at a range of disparity corrugation frequencies to establish a comprehensive picture of the disparity sensitivity functions) was used to determine sensitivity as opposed to judging depth order of two lines. In addition, the stimuli were presented in more naturalistic conditions in which many cues to distance are present (Durgin et al, 1995;Glennerster et al, 1996;Frisby et al, 1996;Bradshaw et al, 1998;O'Leary & Wallach, 1980;Predebon, 1993) and the range of viewing distances included a relatively near one (28.5 cm). We also took care, through the use of artificial pupils, that changes in pupil size and accommodative state, which would normally co-vary with viewing distance, would not also change with viewing distance and thereby cause a change in stereoacuity.…”
Section: Figure 1 About Herementioning
confidence: 99%
“…Using discrete LEDs, Bradshaw et al (1998) found that reliance on monocular motion-parallax cues led to depth underestimation, while reliance on binocular disparity resulted in overestimation. When the two cues were presented together, their outputs appeared to be averaged.…”
Section: Introductionmentioning
confidence: 98%
“…Stereopsis refers to the experience of spatial depth based on the brain's comparison of synchronous and overlapping visual information provided by an organism's paired eyes. Stereopsis is one of the most important depth cues for estimating distance and size for objects in close proximity to oneself ([10]; see also [11]). The loss of spatial information caused by digital mediation makes it harder to interpret spatially complex objects or contexts [12], especially for people of low visuospatial ability [13].…”
Section: Introductionmentioning
confidence: 99%